UPAYA GURU DALAM MENINGKATKAN MINAT BELAJAR ANAK TUNA GRAHITA KELAS III SLB NEGERI SAMBAS TAHUN PELAJARAN 2022/2023 - Novi Aziza; Topik; Syaifudin (Samawa (Sakinah, Mawaddah Warahmah), 2024)
This research was motivated by indications that at the Sambas State Special School in Sebayan Village, it was found that several students were not paying enough attention or were unable to optimally follow the lessons. This happens to students with intellectual disabilities in terms of reading and writing and who are unable to grasp the lessons delivered by the teacher. This condition causes students' interest in learning to be low. Therefore, there are also many demands from parents who want their children to be able to learn calistung (reading, writing, arithmetic) so that parents' demands are very burdensome for mentally retarded children. Parents also don't want their children to be classified as children with special needs, so the parents' wishes are what causes children to be disabled. Grahita must be able to master the same material as regular students. This research has two research objectives, including the following: First, to determine teachers' efforts to increase learning interest in class III mentally retarded children at the Sambas State Special School for the 2022/2023 academic year. Second, to find out the supporting and inhibiting factors in increasing the learning interest of class III mentally retarded children at the Sambas State Special School for the 2022/2023 academic year. This research uses a qualitative approach while this type of research is field research. There are three types of data collection techniques in this research, namely: Interview, Observation and Documentation. Meanwhile, the data analysis techniques used are data collection, data reduction, data display, drawing conclusions and verification. Then the data validity checking techniques used are triangulation (source triangulation) and member check. The results of the research are: First, the efforts made by teachers to increase interest in learning in students with intellectual disabilities are by giving prizes to children who succeed in achieving the expected achievements with motivation in the form of stories or advice. Supporting the development of students' interest in learning with intellectual disabilities can be seen from their habits at school, which can be compared with their habits when they first entered school, as well as their ability to apply something that has been taught by their teacher. Second, the enthusiasm for learning of a mentally retarded student depends on whether he is enthusiastic or not when he first goes to school, where this feeling of enthusiasm is formed because of encouragement or support from parents to go to school. Increasing students' interest in learning is the means and infrastructure that facilitate the learning process so that children do not feel bored and in the learning process when children want to explore their abilities. The need for inadequate facilities and infrastructure is an inhibiting factor in increasing interest in learning among mentally retarded students at SLBN Sambas. A mentally retarded student in the learning process must be in a very supportive mood and environment in order to increase the child's enthusiasm for learning. Both in terms of facilities and infrastructure and environmental conditions.